Detrimental immediate and long-term clinical effects of right ventricular pacing in patients with myocardial fibrosis. (8th February 2021) - Saunderson, C; Paton, MF; Brown, LAE; Gierula, J; Chew, PG; Das, A; Sengupta, A; Craven, TP; Chowdhary, A; Levelt, E; Dall"armellina, E; Witte, KK; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Long-term right ventricular (RV) pacing leads to heart failure or a decline in left ventricular (LV) function in up to a fifth of patients. Objectives: We aimed to establish whether patients with focal fibrosis detected on late gadolinium enhancement cardiovascular magnetic resonance (CMR) have deterioration in LV function after RV pacing. Methods: We recruited 110 patients (84 in final analysis) into two observational CMR studies. Patients (n = 34) with a dual chamber device and preserved atrioventricular (AV) conduction underwent CMR in two asynchronous pacing modes (AOO & DOO) to compare intrinsic conduction with RV pacing. Patients (n = 50) with high-grade AV block underwent CMR before and 6 months after pacemaker implantation to investigate the long-term effects of RV pacing. Results: The three key findings were: 1) Initiation of RV pacing in patients with fibrosis, compared to those without, was associated with greater immediate changes in both LV end-systolic volume index (LVESVi) (5.3 ± 3.5 vs 2.1 ± 2.4 mL/m2; p < 0.01) and LV ejection fraction (LVEF) (-5.7 ± 3.4% vs -3.2 ± 2.6%; p = 0.02); 2) Long-term RV pacing in patients with fibrosis, compared to those without, was associated with greater changes in LVESVi (8.0 ± 10.4 vs -0.6 ± 7.3 mL/m2; p = 0.008) and LVEF (-12.3 ± 7.9 vs -6.7 ± 6.2%; p = 0.012); 3) Patients with fibrosis did not experience an improvement in quality of life, biomarkers or functional class after pacemaker implantation. Conclusions: Fibrosis detected on CMR is associated with immediate and long-term deterioration in LV function following RV pacing and could be used to identify those at risk of heart failure prior to pacemaker implantation.